Forward versus backward semantic priming: What movement dynamics during lexical decision reveal. Issue 7 (July 2018) - Kang, Sean HK; Eglington, Luke G; Yap, Melvin J
Separate processes underlying forward (e.g., crescent MOON) and backward (e.g., office POST) priming have previously been inferred from button-press lexical decision response times, with an automatic prospective mechanism and a strategic retrospective mechanism presumed responsible for forward and backward priming, respectively. We tracked hand/mouse kinematics during lexical decision, and found that forward, backward, and symmetrical (e.g., cat DOG) priming exhibited different movement trajectories, with the effect of forward priming emerging earlier than that of backward priming and with symmetrical priming taking the lead around the time when the backward priming effect came online. The findings provide strong converging evidence for different mechanisms driving forward and backward priming, and demonstrate that continuous kinematic measures can shed light on cognitive processes as they unfold in real time.